Targeting Mobilization of Ferrous Iron in Pseudomonas aeruginosa Infection with an Iron(II)-Caged LpxC Inhibitor - Blank, Brian R. (ACS Infect Dis, 2019)
Iron is essential to all life, and competition for this vital nutrient is central to host–pathogen interactions during infection. The opportunistic Gram-negative pathogen Pseudomonas aeruginosa utilizes a diverse array of iron-acquisition strategies, including those enabling import of extracellular ferrous iron. We hypothesize that soluble and redox-active ferrous iron can be employed to activate caged antibiotics at sites of infection in vivo. Here we describe new chemistry that expands the application of our laboratory’s Fe(2+)-activated-prodrug chemistry to cage hydroxamic acids, a class of drugs that present manifold development challenges. We synthesize the caged form of a known LpxC inhibitor and show that it is efficacious in an acute P. aeruginosa mouse-lung infection model, despite showing little activity in cell-culture experiments. Overall, our results are consistent with the Fe(2+)-promoted uncaging of an antibacterial payload at sites of infection in an animal and lend support to recent reports indicating that extracellular pools of ferrous iron can be utilized by bacterial pathogens like P. aeruginosa during infection.